FoxA1 is a Key Mediator of Hormonal Response in Breast and Prostate Cancer - Robinson, Jessica; Carroll, Jason (Frontiers in Endocrinology, 2012)
The hormonally regulated breast and prostate cancers are the most common cause of cancer in females and males respectively. FoxA1 acts as a pioneer factor for both androgen and oestrogen receptor, dictating the binding location and therefore function of these transcription factors. Despite being an essential protein for the transcriptional activity of both ER and AR, its interplay with these two nuclear receptors is not the same, yet in both malignancies, it plays a pivotal role from early stage cancer through to drug resistant and metastatic disease. Due to this key role in mediating ER and AR function, FoxA1 is not only an attractive therapeutic target but could potentially function as a novel biomarker.